Frank P. Casa, The dramatic craftsmanship of Moreto. Harvard University Press, Cambridge, Massachusetts, 1966; 187 pp. - Kersten, Raquel (El Colegio de México, 1972)
Se reseñó el libro: The dramatic craftsmanship of Moreto.